Modelación Integrada de Sistemas Socio-ecológicos Complejos: Caso de Estudio la Ecorregión de la Mojana - Villegas Gonzalez, Paula Andrea; Florez Florez, Maria Juliana; Triviño León, Nathaly; Escobar, Jorge Alberto; Obregón Neira, Nelson; González Méndez, Alex Mauricio; González Salazar, Ramon Eduardo (Ingeniería, 2016)
Context: It was observed that the modeling of complex socio-ecological systems based on Agent-Based Simulations has the advantage of allowing the integration of different processes, scales, variables and the possibility to generate scenarios with actors in the context of the modeling with stakeholders. Method: A computational tool for planning and support of decision-making processes related with water resources management, specifically in the case of floods in the Mojana ecoregion (Colombia) is designed along with social participation workshops related with beliefs, values, social networks and resilience. Results: The model has two components: the first one represents the hydrodynamic of flooding by means of the numerical platform ISIS 2D. The second one, regarding the social aspects of the region, is handled via agent systems modeling. Both schemes are integrated into the NetLogo platform. Conclusions: The integrated modeling of complex socio-ecological systems allow us to visualize the behavior of the population and the natural resources in a territory, contributing to the design of policies and educational processes involving different disciplines and actors. Future work will focus on regional modeling and the analysis of the impact produced by the use of these tools.